Mary Norton of New Jersey, Congressional Trailblazer - Porter, David L., 1941- (Fairleigh Dickinson University Press, 2013)
The book tells the compelling story of Mary Norton of New Jersey, who served 13 terms in the U.S. House of Representatives (1925-1951) and was the first female elected to the U.S. Congress from the Democratic Party, an eastern state, or urban section east of the Mississippi River and to chair a major congressional committee. Besides chairing the District of Columbia Committee, she steered through the Labor Committee and the House the landmark Fair Labor Standards Act of 1938 and inspired young women of limited educational and meager financial background to participate in pol.